MODEL KOMUNIKASI FASILITATOR DALAM PELATIHAN MODERASI BERAGAMA BAGI PARA PENYULUH AGAMA - Rubi Rubiyanah; Hesti Kusumaningrum; Abdul Jalil; Eko Purwanto (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2026)
Religious tension and intolerance remain challenges in plural societies, highlighting the need for effective  religious moderation training. This Study aims to analyze facilitator communication strategies in religious moderation training and the implementation of the Seven C's communication model in internalizing tolerance and diversity values. The research employs a qualitative approach  with a case study design, collecting data trough observations, in-depth interviews, and documentation involving facilitators and participants. Findings indicate that facilitators implement systematic and interactive communication strategies through two-way dialogue, storytelling, case simulations, group discussions, and visual media. The application of the Seven C's principles clarity, conciseness, credibility, consistency, courtesy, concreteness, and consideration enhances participant's  understanding, engagement, empathy, and creates an facilitators as social change agents capable  of transferring moderation values cognitively, affectively, and behaviorally.